Quick Blood Volume (Qb) and Ultra Filtration Ureum at Haemodialysis Patient - Syamsul Arif S. N; Rodhi Hartono; Nina Indriyawati (Poltekkes Kemenkes Semarang, 2012)
This study to determine the effect of the quick blood volume (Qb) to the process of ultrafiltration hemodialysis urea in action research is a Quasi experiment research with pre and post test desaign. The number of samples in this study were 54 people. Data processed by Anova test one path to find the differences between RRU and also know the difference decreased levels of blood urea between the three treatment groups are setting Qb 150, 175 and 200 ml/min. ANOVA test RRU significance value (p: 0.26) and the significance of decreased levels of blood urea (p: 0.52) which means there is no significant difference in the value of RRU and also decreased levels of blood urea between the three treatment groups are setting Qb 150, 175 and 200 ml /min.